آفاق تبني معايير المحاسبة الدولية للقطاع العام(IPSAS) في المؤسسات العمومية الجزائرية--عينة من المؤسسات العمومية بولاية الوادي- - كير, نصيرة; سعداني, نجوى (University of eloued جامعة الوادي, 2019)
"تهدف هذه الدراسة إلى تبيان آفاق تبني معايير المحاسبة الدولية للقطاع العام في المؤسسات العمومية الجزائرية حيث تناولت في شقها النظري تقييم واقع المحاسبة العمومية في الجزائر ذات الطابع غير الربحي، ومعرفة متطلبات تبني معايير المحاسبة الدولية في القطاع العام وتحديات تطبيقها، كما خلصت الدراسة في شقها الميداني المتضمن توزيع إستمارة استبيان على عينة من المؤسسات العمومية بولاية الوادي وتحليلها بإستخدام البرنامج الإحصائي SPSS، لمعرفة استجابات أفراد العينة (آمرين بالصرف، مراقبين ماليين، محاسبين عموميين )، وتحديد فروق في استجابات هذه الأخيرة حسب البيانات الشخصية والمهنية. وتوصلت الدراسة إلى مجموعة من النتائج أهمها موافقة أغلبية أفراد العينة على أن نظام المحاسبة العمومية يعاني من قصور في عملية الإبلاغ المالي الحكومي نتيجة لعدم استجابته للتغيرات العالمية، مع ضرورة تحديث وإجراء إصلاح شامل لنظام المحاسبة العمومية في مختلف جوانبه القانونية والتقنية بما يتوافق مع هذه المعايير، مراعاة في ذلك خصوصية البيئة الجزائرية بما يضمن تكييفه مع الممارسات العالمية، وعدم وجود فروقات في استجابات أفراد العينة. ""The objective of this study is to clarify the prospects for adopting the International Public Sector Accounting Standards (IPSAS) in the Algerian public institutions. The study tackled the assessment of the state of public accounting in Algeria with a non-profit nature. The study also examined the requirements of adopting international accounting standards in the public sector and the challenges of their application. Which included the distribution of a sample questionnaire on a sample of public institutions in the Wilayat of Al-Oued and its analysis using the statistical program SPSS, to identify the responses of the sample members (ordonnater, Financial control and public accountants) and to identify differences in the responses of the latter Nat personal and professional. The study reached a number of results, the most important of which was the approval by the majority of the respondents that the public accounting system is deficient in the government financial reporting process as a result of its failure to respond to global changes. The general accounting system in all its legal and technical aspects must be updated and carried out in accordance with these standards. Taking into consideration the specificity of the Algerian environment in order to ensure that it is adapted to international practices and that there are no differences in the responses of the sample members "
مذكرة ماستر محاسبة
Keywords: محاسبة عمومية، معايير المحاسبة الدولية للقطاع العام، أساس نقدي، أساس الاستحقاق.; General Accounting, International Public Sector Accounting Standards (IPSAS), Cash Basis, Maturity Basis.